Of Cocaine And Scaffold Bars: A Critique of The Myth of Mental Illness By Thomas S Szasz (Existential Analysis: Journal of the Society for Existential Analysis, 2014)
The Myth of Mental Illness remains a seminal text within psychiatry, psychology and psychotherapy. Fifty-four years on from first publication, Szasz' contentions concerning 'mental illness' are examined in light of current understandings and research. It is suggested that there can indeed be 'mental illness' but that this may nonetheless lead to compassionate practice.
Keywords: Mental illness; Neurology; Szasz; Anti-psychiatry; Hysteria; Conversion disorders